Ultimate customer loyalty's Holy Grail - Ow, Mun Waei (2017)
This research aims to identify the causal factors of ―Ultimate Customer Loyalty‖—The Holy Grail of Customer Loyalty. Implementing these factors should enable a business enterprise (an entity) to increase its market share and achieve long-term customer loyalty, and, hence, profitability. Firstly, this study explains the conceptualization of three distinct states of the Customer Loyalty Continuum: 1) No customer loyalty (0% loyalty), 2) Simple Customer Loyalty (0% loyalty<Simple Customer Loyalty<100% loyalty), and 3) Ultimate Customer loyalty (100% loyalty i.e., totally loyal). Secondly, this study sets out mechanisms to explain how customers shift from the Customer Satisfaction state to the Ultimate Customer Loyalty state, through the mediating roles played by Simple Attitudinal Customer Loyalty and Simple Behavioural Customer Loyalty. Thirdly, this research focuses on two prominent constructs, namely Consumer Spending Self-Control, and Attractiveness of Alternatives as the moderators in the Satisfaction—Loyalty Link. The research context is mobile phone brands because mobile phones are high involvement products. A positivist approach was adopted in the research, utilizing four hundred and five (405) personally administered questionnaires which were distributed to respondents through purposive sampling: respondents who own and have repurchased mobile phones. A pre-test of three (3) experts and three (3) targeted respondents from the non-scientific community and a pilot test of 100 respondents was conducted. Consequently, the data collected were analyzed using SmartPLS-SEM. Results show that Customer Satisfaction has a positive effect on Simple Attitudinal Loyalty and Simple Behavioural Loyalty. Both Simple Attitudinal Customer Loyalty and Simple Behavioural Customer Loyalty have positive effects on Ultimate Customer Loyalty. In addition, both Simple Attitudinal Loyalty and Simple Behavioural Loyalty are found to have mediating effects between Customer Satisfaction and Ultimate Customer Loyalty. Finally, Consumer Spending Self-Control is found to strengthen the Customer Satisfaction—Simple Attitudinal Loyalty Link; while Attractiveness of Alternatives is found to weaken the Customer Satisfaction—Simple Attitudinal Customer Loyalty Link. Theoretical contribution to the field is achieved through the verification of the framework; and its practical contribution lies the viable basis by which business entities can enhance customer loyalty for their products/services; and help marketers to differentiate between spurious and ultimate customer loyalty.